Predictability and predictors of volatility smirk: a study on index options - Pathak, Rajesh; Mitra, Amarnath (Business: Theory and Practice, 2017)
The purpose of this study is to examine the presence of volatility smirk anomaly in index options and its predictability for future returns. The study tests the temporal properties of volatility smirk and further explores the factors determining the anomaly. The daily volatility smirk is computedfor the period 2004–2014 and the first lag of smirk is used in generalized least square (GLS) estimation framework, with set of control variables in two different specifications, to test the predictability as well as the determinants of volatility smirk. The study reports significant presence of volatility smirk in index options with an auto–regressive structure. Smirk predicts marginal returns and the predictability is robust to the control of major risk factors. It is also found that open interest of calls and puts, along with market risk premium and momentum premium, act as significant predictor of volatility smirk. The results are helpful in enhancing returns on investment in Index based funds and designing options strategies from the perspective of volatility risk. The study is first of its kind in the Indian market examining the reasons and consequences of existence of volatility smirk in index options.